Life cycle CO2 emissions from power generation using hydrogen energy carriers. (23rd April 2019) - Ozawa, Akito; Kudoh, Yuki; Kitagawa, Naomi; Muramatsu, Ryoji
Abstract: Hydrogen energy carriers such as liquid hydrogen (LH2 ), methylcyclohexane (MCH), and ammonia (NH3 ) are promising energy vectors in the clean energy systems currently being developed. However, their effectiveness in mitigating environmental emissions must be assessed by life cycle analyses throughout the supply chain. In this study, while focusing on hydrogen energy carriers, life cycle inventory analyses were conducted to estimate CO2 emissions from the following types of power generation plants in Japan: a hydrogen (H2 ) mono-firing power plant using LH2 or MCH that originated from overseas renewable electricity; and NH3 co-firing with fossil fuel and NH3 mono-firing power plants using hydrogen energy carriers that originated from overseas natural gas or renewable electricity. Parameters related to the supply chains were collected by literature surveys, and the Japanese life cycle inventory database was primarily used to calculate the emissions. From the results, CO2 hotspots of the target supply chains and potential measures are identified that become necessary to establish low-carbon supply chains. Highlights: Japan is in the process of transitioning to hydrogen based energy systems. Life cycle CO2 emissions from different hydrogen energy carriers were studied. There are several steps in the process where CO2 emissions could be further reduced. Development of low-carbon systems would have many environmental benefits.